Estágio de intemperismo da cobertura superficial na superfície geomorfológica V (Clevelândia/ PR) - Planalto das Araucárias - Bertuol, Elizandra Carla (2014)
The present study examined the stage of weathering of the surface coverage for the geomorphologic surface V, located in Clevelândia (PR) in the field of the Araucária Plateau. To this end, we analyzed the characteristics of the physical and chemical properties of materials in the profile; was determined from the free, total, and the crystalline iron and the total chemical ten (10) major oxides by X-ray fluorescence finally, there is the micro morphology organization of materials. The weathering profile presented more than 710 cm of exposed material, with gradual transition horizons: A (0-20 cm), AB (20-60cm), BA (60-110 cm), Bw1 (110-210 cm), Bw2 (210-350 cm), BC (350-470 cm) and CB (470- 540 cm) and C (540 - 710+ cm). The characterization of physical and chemical attributes of the weathering profile showed native soil cover, with features Oxisols red with acric character. The mineralogical analysis of the material indicated weathering stage characterized by partial hydrolysis environment, the monossialitization type. Associating soil and geochemical characteristics, one realizes that it is weathering profile whose evolutionary process is to ferruginization. The results confirm the hypothesis that the surface V was prepared by the action of etchplanation from the lowering of the substrate by isovolumetric loss generating planing.